A comparative study of various fibers and waste plastic fiber reinforced concrete - Nibudey, Ram N.; Nagarnaik, Prashant B.; Parbat, Dhananjay K.; Pande, Anant M. (Journal of Structural Engineering, 2025)
The fiber reinforced concrete is more ductile and serviceable than conventional concrete. The fibers of various origins are in demand in concrete matrices. Industrial activities are associated with significant amount of non-biodegradable solid waste like waste plastic being among the most prominent. In this paper the readily available discrete fibers of different origin (steel, carbon, polypropylene, coir and jute) and manually obtained PET fibers of waste mineral water bottle were used for reinforcing the concrete. The M20 grade of concrete was designed using Portland Pozzolana cement (fly ash based) and locally available aggregates. A total of 180 specimens with volume fractions of fibers in the rage of 0.0, 0.5, 1.0, and 1.5 % were prepared for the experimental study. The curing age of 28 days for all the concrete mixtures were followed in this work. The experimental results of cube compressive strength, split tensile strength, flexural strength and toughness indices of selected fibers are presented. Although, different origin fiber cannot be compared at same platform, the object of this study was to analyse the feasibility PET fibers in concrete and see where these fibers stands as compared to others. This study insures that, the PET fibers obtained from waste mineral water bottles are feasible to add in concrete and give a good approach to reduce the cost of materials and solve some of the solid waste problems posed by non biodegradable plastics.